(untitled) (Research, Society and Development, 2021)
Introduction: adolescence has been seen in the Brazilian and worldwide scenario as a period of intense and abrupt physical, emotional and mainly behavioral changes. With the advent of AIDS and the emergence of sexually transmitted infections (STIs) – important causes of morbidity and mortality in Brazil – the health system expanded the view of risk factors associated with transmissible diseases and brought to the discussion the issue of vulnerability and sexuality. Objective: to explain about changes in sexual behavior among young people, even in the face of greater debate on the subject, and the incidence of STIs, which remains high. Methodology: this is a narrative literature review. The search was carried out through online access in the National Library of Medicine (PubMed MEDLINE), Scientific Electronic Library Online (Scielo), Cochrane Database of Systematic Reviews (CDSR), Google Scholar, Virtual Health Library (BVS) and EBSCO databases Information Services, October 2021. Results: there is a significant change in the behavior of young people regarding sexual health and the way they relate to their partners. In addition, it is noted that the current generation is more exposed, given that, due to the advent of the internet and, later, relationship applications, there was a revolution in the forms of interpersonal interaction, bringing many facilities, especially for the LGBTQIA+ population, who found in these virtual instruments a safe space for affective and sexual contact. Final considerations: it is important that young people are guided in relation to their sexual practices. In addition to the study of anatomy, sex education provides access to information about different aspects of sexuality. From it, people become able to exercise their sexual and reproductive desires, being informed about their health, given that sexuality is linked by different dimensions, such as biological, social and cultural.